Gastronomi dan Sakralitas Budaya Kuliner “Kolok Goblok” menuju Warisan Budaya Tak Benda (WBTB) Kabupaten Malang - Maulia Dyah Risanti; Marshanda, Isa Aini Yushan; Sabila, Isna Sal; Hartono (Brawijaya Journal of Social Science, 2025)
The purpose of writing this article is to explore the culinary culture of Kolak Goblok as part of the culinary cultural heritage of Poncokusumo village, Malang Regency, East Java. Specifically, the study examines in more depth the history, manufacturing process, and cultural and social values ​​contained in Kolok Goblok. Kolok Goblok is a traditional culinary that has deep historical, cultural, and social values. A dish made from pumpkin steamed with grated coconut and brown sugar, is not just food, but has an important role in traditional rituals and community celebrations. This study uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews and documentation. Thirteen respondents were involved in the data collection process, including 3 Pokdarwis, 2 traditional institutions, 1 village official, 1 village head, 2 community leaders, 3 culinary preservationists, and 1 kolok goblok maker. The analysis method used in this study is descriptive analysis, which aims to provide a comprehensive picture of the existence and meaning of Kolok Goblok for the Poncokusumo community. The results of the study show that Kolok Goblok is not just a traditional food, but also a symbol of regional identity that represents local cultural values. This dish is part of a cultural expression that has been passed down from generation to generation and is still maintained today. In addition, Kolok Goblok has great potential in supporting culture-based tourism in Malang Regency